Ayat-Ayat Kepemimpinan dalam Tafsīr Al-Munīr Perspektif Tafsīr Maqāṣidī Abdul Mustaqim - Rendi, Rendi Irawan; Eka Prasetiawati; Muhammad Nur Amin (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
Leadership is a fundamental aspect of human civilization and a central theme in Islamic teachings. The Qur'an addresses various dimensions of leadership through terms such as khalīfah, imāmah, and ulū al-amr. This study aims to explore the concept of leadership in Islam by analyzing Qur’anic verse QS. al-Baqarah [2]:30 through the lens of tafsīr maqāṣidī as developed by Abdul Mustaqim, using Tafsīr al-Munīr by Wahbah al-Zuḥaylī as the primary interpretive source. Employing a qualitative library research method, this paper focuses on the linguistic, semantic, and thematic analysis of the verse to uncover ethical and spiritual values embedded in the Qur’anic discourse on leadership. The findings reveal that QS. al-Baqarah [2]:30 offers a comprehensive framework for Islamic leadership rooted in divine trust (amānah) and oriented toward achieving public benefit (maṣlaḥah). Through a maqāṣidī approach, the verse reflects key principles such as environmental stewardship (ḥifẓ al-bī’ah), protection of life (ḥifẓ al-nafs), and intellectual empowerment (ḥifẓ al-‘aql). These dimensions highlight the leader’s responsibility to preserve ecological balance, ensure human dignity, and promote education and critical thinking. The study concludes that Qur’anic leadership transcends political authority, emphasizing moral integrity, accountability, and alignment with the higher objectives of Islamic law. By contextualizing Qur’anic principles within contemporary challenges, this paper contributes to the development of a relevant, ethical, and sustainable model of Islamic leadership.